PENGEMBANGAN ALAT PERAGA SISTEM PENCERNAAN MANUSIA DENGAN MEMANFAATKAN BARANG BEKAS UNTUK SISWA KELAS VIII SMP/MTs - Anggiya Putri Ramadani; Eko Wulandari; Pitri Handayani; Pitri Handayani (BIOCOLONY, 2023)
The background of this research used that teachers at SMP N 45 Merangin have never develop science teaching aids on human digestive system materials made from used materials such as used books and used printing paper. Teachers only use student worksheets (LKS) for teaching, limited props provider at school. This study aims to develop science teaching aids on the material of the human digestive system' by utilizing used goods for class VIII student of SMP/MTs that are valid and praktical. This study used methods of the 4-D model, namely define, design, develop and disseminate. The research subjects consisted of 5 people of produce validation, namely content feasibility, language, presentation and graphics and practicality tests were carried out by 1 science teacher and 17 students of SMP N 45 Merangin. Based on the results of this study, a product in the form of teaching aids for the human digestive system was produced from used goods such as used books and used printing paper which were very valid from the aspect of presentation and graphics with and average value of 96,1%. The results of the validation of the booklet from the aspects of content feasibility, language, presentation and graphics with an average value of 98,75% are in a very valid category. The resulting visual aids and booklets were also stated to be practical by teachers and student both in terms of ease of use, learning time and attractivenes with an average score of 3,33 for teachers and 3,26 for students. So itu can be concluded that teaching aids for the human digestive system from used goods and booklets are stated to be very valid and practical.